2012
DOI: 10.1007/s00338-012-0926-8
|View full text |Cite
|
Sign up to set email alerts
|

Locally accelerated growth is part of the innate immune response and repair mechanisms in reef-building corals as detected by green fluorescent protein (GFP)-like pigments

Abstract: Homologs of the green fluorescent protein (GFP) are a prevalent group of host pigments responsible for the green, red and purple-blue colours of many reefbuilding corals. They have been suggested to contribute to the striking coloration changes of different corals species in response to wounding and infestation with epibionts/parasites. In order to elucidate the physiological processes underlying the potentially disease-related colour changes, we have analysed spatial and temporal expression patterns of GFP-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 40 publications
7
101
2
Order By: Relevance
“…In the polyps of P. damicornis, we have observed that the oral disk was delimited by a concentrated ring of GFP-like molecules. According to D'Angelo et al (2012), GFP-like proteins are concentrated in areas of growth and accelerated cell proliferation in several coral species (Porites lobata, Montipora foliosa, Acropora pulchra/polystoma) and could be used as a biomarker of locally accelerated growth and tissue regeneration. In the forming tissue balls of P. damicornis, we did not record any spatially differentiated pattern of distribution of GFP-like molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the polyps of P. damicornis, we have observed that the oral disk was delimited by a concentrated ring of GFP-like molecules. According to D'Angelo et al (2012), GFP-like proteins are concentrated in areas of growth and accelerated cell proliferation in several coral species (Porites lobata, Montipora foliosa, Acropora pulchra/polystoma) and could be used as a biomarker of locally accelerated growth and tissue regeneration. In the forming tissue balls of P. damicornis, we did not record any spatially differentiated pattern of distribution of GFP-like molecules.…”
Section: Discussionmentioning
confidence: 99%
“…DNA synthesis was detected in 2-4 % of the Symbiodinium dinoflagellate endosymbionts of Montipora capitata, via BrdU (50 lM) labeling during 48 h (Santos et al 2009). In another study, mitotic activity was assessed by expression of the conserved Proliferating Cell Nuclear Antigen (PCNA) protein in the species Montipora foliosa and Acropora pulchra, following creation of a lesion (D'Angelo et al 2012). But in both cases, the spatial distribution of the proliferation activity was determined only at the level of the colony, comparing top versus underside and margin versus inner area of plate-forming Montipora corals, and comparing apex versus branch of branching Acropora corals.…”
Section: Introductionmentioning
confidence: 99%
“…While reef-building corals have the capacity to produce significant quantities of FPs (Leutenegger et al 2007), the function of FPs is unknown. As a result of ambiguous data which may be caused by the diversity of FPs and corals, hypothesized roles for the function of FPs include photoprotection (Salih et al 2000, Roth et al 2010, Smith et al 2013, antioxidant activity (Mazel et al 2003, Bou-Abdallah et al 2006, Palmer et al 2009a), photosynthesis enhancement (Salih et al 2000), Symbiodinium regulation (Field et al 2006), part of an immune response (Palmer et al 2009b, D'Angelo et al 2012, camouflage (Matz et al 2006b), maintenance of color diversity (Dove et al 2001), and attraction of free-living Symbiodinium (Hollingsworth et al 2004). It is possible that different FPs could have different roles, particularly in distinct environments such as shallow or mesophotic habitats.…”
Section: Introductionmentioning
confidence: 99%
“…The 495 to 589 nm peaks on the 2nd derivative of both species (see Figures 4 and 5) might be a consequence of the presence of GFPs on this species as it has been demonstrated in the past [47]. For instance, recently D'Angelo et al found GFP's emitting at 490 nm and 584 nm in Porites lobata and Acropora pulchra, respectively [50]. While a possible contribution of GFPs to the reflectance signals of both species cannot be discarded, and no attempts were made to quantify this, we postulate this contribution of GFPs within the blue region, particularly below 450 nm, might be minimal as the emission peaks of GFPs are usually within the green and red regions of the visible spectrum [49].…”
Section: Porites Poritesmentioning
confidence: 60%